Immigration passport visa manual. (Diplomatic Post Pub., 1994)
"The Manual came off the press in 1987. It has been updated and repaired several times since then. This edition of Manual came off the press in September 1994." The Immigration Passport Visa Manual seeks to help disseminate public information to serve the needs of international travelers. It contains advice tips, regulations and public documents from 58 countries with the assistance of their embassies, consulates and home government ministries or offices. It is a recommended reference for travel agencies, travel executives, prospective immigrants, tourists, job seekers, contract workers, nurses, seamen, domestic helpers, professionals and other individuals who wish to see or try their fortune in different lands. It can be very useful to those who live in remote areas like municipalities, cities and provinces where there are no embassies, consulates or extension offices of the Department of Foreign Affairs, or reputable travel agencies."